Analysis of Factors Influencing Repeat Migration Decisions of Indonesian Migrant Workers - Try Rakhma Rizky; Luluk Fadliyanti; Vici Handalusia Husni (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This research aims to empirically test the influence of income, education, number of family dependents, age, and marital status on the repeat migration decisions of Indonesian migrant workers in Sakra village. The sample of this research is Indonesian migrant workers in Sakra village. Data collection was carried out by distributing questionnaires directly to 40 Indonesian migrant workers in Sakra village. The statistical method uses logistic regression analysis (binary logistic), Wald test, and pseudo R² with the results of income, education, and number of family dependents having a positive influence on the decision to re-migrate Indonesian migrant workers in Sakra village, age having a significant negative influence and marital status having a significant influence positively influencing the decision to re-migrate Indonesian migrant workers in Sakra village.